Effect Of Rheumatic Exercises On Pain Levels In Rheumatic Patients In The Working Area Of Kalijudan Public Health Center Surabaya - Rindi Antika Putri; Mohammad Najib; Irfany Nurul Hamid; Sari Luthfiyah; Mazlinda Musa Musa (International Journal of Advanced Health Science and Technology, 2025)
Rheumatism is a condition marked by joint inflammation, swelling, and pain, often causing limitations in daily activities and decreasing productivity. Prolonged symptoms, especially over 10 years, may lead to joint damage, making patients reliant on others and impacting their social and economic functioning. This study aims to examine the effect of rheumatic exercises on pain levels among rheumatic patients in the Kalijudan Public Health Center area, Surabaya. The research employed a pre-experimental one-group pretest-posttest design involving 31 participants selected through purposive sampling. Rheumatic exercises were the independent variable, while pain levels were the dependent variable, measured using the Numeric Rating Scale (NRS). The data were analyzed using the Wilcoxon test with a significance level set at p<0.05. The results showed a Wilcoxon test value of 0.000, indicating a statistically significant difference in pain levels before and after the intervention. These findings demonstrate that rheumatic exercises effectively reduce pain in rheumatic patients. The study concludes that implementing rheumatic exercise programs can be a beneficial non-pharmacological intervention to manage pain in patients with rheumatism, particularly in community health settings like the Kalijudan Public Health Center.